Water level profile calculation using HEC-RAS / Nadia Tulos - Tulos, Nadia (Faculty of Civil Engineering, 2004)
Computer programmers have been used by engineer since 1960’s to perform calculation to determine channel flow characteristics. Engineers design drainage channel, storm sewer or culvert for example base on the calculation of water surface profile. Even though the calculation can be done manually but it is not suitable because it takes longer duration. Because of this many software have been develop since that. Nowadays there are much software in market such as HEC-2, HEC-6, HEC-5 and HEC-FDA. Each of the software has its own used for example HEC-5 that is used for simulation of flood control and conservations system. HEC-2 is used to calculate water surface profile for any cross-section. HEC-RAS is one of the numerical simulations that are used to analyze water surface profile. HEC-RAS River Analysis System is a computer program that is developed by U.S Army Corps of Engineers Hydrologic Engineering Center. HEC-RAS numerical simulation for Klang River shows that the water level calculated from the software provide nearly the same water level from the data collection from Department of Irrigation (DID).The limitation for this study is that steady flow analysis is done for simulation and Klang River is fixed bed. The parameter for calibration is Manning’s Roughness, n and the value is 0.01.This Manning’s roughness, n for Klang River represents trowel finish, concrete line up channel. HEC-RAS can be used to predict the water level profile after calibration and verification of the parameters.